Perbandingan Teknologi Pengeringan Kopra dengan Metode Indeks Kinerja Komposit - Mohamad Yani; Naufal Ali Hamid; Tyara Puspaningrum; Ika Amalia-Kartika; Andes Ismayana (Jurnal Ilmu Pertanian Indonesia, 2022)
The drying performance technology is one of the most critical operations in copra production. This study aims to identify various drying methods in copra production and determine the best copra drying method based on the criteria of drying operation, environmental impact, and copra product quality. The research was carried out with the stage of identifying the drying methods of copra through literature studies and secondary data collection and continued with the stage of determining the best drying method using the composite performance index (CPI) method. Of nine drying methods, six range were identified as coconut processing scale 20–1200 kg, copra drying temperature 40–70°C, drying time 7.9-48 hours, drying rate 1.05–5.70%/hour, energy use 110.7–32140 kJ/kg-product, and the emission of 0.1–34.074 kg-CO2/kg-product. The nine methods of drying copra produce good quality copra based on copra product standards. Based on the calculation of alternative values using the CPI method, it has been shown that the best drying method was using a dryer with a drying temperature of 68°C and a drying rate of 5.70 %/hour. This drying method uses the energy of 14824 kJ/kg product and produces an emission value of 1.25 kg-CO2/kg product. The copra produced by this drying method gives 5% moisture, 60% oil, and 1% free fatty acid. Keywords: coconut, composite performance index, copra, drying technology